Axial skeletogenesis in human autosomal aneuploidies: A radiographic study of 145 second trimester fetuses. Issue 3 (21st December 2015) - Castori, Marco; Servadei, Francesca; Laino, Luigi; Pascolini, Giulia; Fabbri, Romano; Cifani, Anna Elisabetta; Sforzolini, Giovanna Scassellati; Silvestri, Evelina; Grammatico, Paola
Abstract : Autosomal aneuploidies associate with multiple minor skeletal defects, which, in fetuses, are best appreciated post‐mortem after specific anatomic preparations. The present study was aimed to define patterns of skeletal anomalies in autosomal aneuploidies at standard radiology in second trimester fetuses by comparing findings in and among genotypes and gestational ages. Aneuploid fetuses were selected for availability of radiographs of various axial and non‐axial structures, mainly homeotic transformations, vertebral clefts, vertebral segmentation and ossification defects, absent/hypoplastic nasal bone, premature talar calcifications, and selected appendicular anomalies. Eighty six fetuses with trisomy 21, 39 with trisomy 18, eight with trisomy 13, six with triploidy, and six with rare autosomal aneuploidies were identified, 75.2% showing an abnormal costo‐vertebral pattern, mostly cervical ribs, absence of the 12th thoracic ribs and posterior homeotic change. Clefting was observed along the entire spine, especially sagittal lumbar clefts, and coronal thoracic clefts. Four different types of vertebral clefting were identified, including type 1 (butterfly), type 2 (incomplete inferior), type 3 (incomplete superior), and type 4 (complete). Attenuation of clefting by gestational age was observed in trisomy 21 and 18. These findings define more clearly the pattern of perturbed morphogenesis in aneuploidy as a type of amplified developmental instability with pleiotropic effects on skeletogenesis. © 2015 Wiley Periodicals, Inc.